ITIL Implementation: Information Technology Incident Management for a Chemical Importing Company - Aparicio-Lecca, Martin; Arce-Holgado, Adrian; Sierra-Liñan, Fernando (LACCEI, 2024)
Many organizations dedicated to the importation of chemical products do not have a proper implementation of IT incident management procedures. In addition, they do not have the knowledge to be able to resolve incidents correctly within their organizations, and by not being clear about their processes they cannot have a better application to make a continuous improvement, since technology is constantly advancing. In the present investigation, by means of the methodology ITIL version 3. 0, which uses good practices that give the appropriate parameters to apply it to any entity, so that the research objectives are the resolution time, the number of tickets resolved, the services covered and user satisfaction, it is observed that the IT area lacks processes being a current need, The type of study that is handled in this research is applied, so the reason for the problem is incident management, being the quantitative approach that focuses on data collected, therefore, the design is experimental where the variables are related to the research problem. In addition, the level is explanatory to collect information through the population of 50 people working in the organization, focused on non-probabilistic convenience sampling. Likewise, it is focused on improving the management of incidents where it has allowed to identify up to this moment major deficiencies in the delivery and management of these to all areas. To perform the reliability, the type of content was validated where the Kolmogorov-Smirnov normality test gave a favorable result indicating that the instruments are reliable.